STATE WELFARE STATE SOCIAL AND SOCIETY: SOCIAL POLICIES AND THE ISSUE OF POVERTY IN A PERSPECTIVE MULTIDISCIPLINARY - Batista, Elicardo Heber de Almeida [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
Theme of poverty has come to occupy a prominent place on the national and international political agenda, and various governments, including Brazilians, have expanded programs and poverty reduction policies, at least in the final years of the twentieth century, and in a more expressive way, after the decade of 90. Our objective is to systemize and present the concept of poverty and the indicators of this harmful social phenomenon. We also discuss concepts that bring important elements of social disadvantage, in particular the exclusion and social marginalization Whereas different poverty complex prospects, to be addressed in discussion throughout the text, shall result in a proposal for the approach to this concept and to achieve a better understanding of specific national realities in Brazil, markedly related to deal with local experiences scarred by intractable poverty. In addition, the text is seeking to widen the theoretical discussion from empirical evidence containing indicators on poverty and social exclusion in Europe, particularly in the case of Portugal.
Keywords: Poverty; Marginalization; Social exclusion; Social policies